From print to digital: a study on conceptions and transformations in the reading habit (Research, Society and Development, 2020)
This study presents the conceptions and transformations in the habit of reading, considering the changes in paradigms, and their variations that have occurred in the way of reading over the years, having as its beginnings the scrolls until arriving at the incipient e-books. With the advent of technological advances and the taking of the digital age, reading and writing has become a totally innovative agent, as new mechanisms for reading and writing are available, as evidence, there is digital literacy, mastery of technique and ability through digital devices that are effective in the multiplicity and development of reading. In light of this, the study also addresses discussions that present issues pertinent to the fate of the printed book in the face of the growth of the digital book. As a literary review, it is anchored in Chartier (1999), Fisher (2009) who warn about the purposes of reading that, above all, consist in communicating, (Xavier, 2002; Coscarelli; Ribeiro, 2007), who developed research on reading and writing in a virtual environment, assuming that hypertext, digital texts, and new forms of reading and writing have largely occupied the life of contemporary society. Finally, the relevant foundations of Eco, Carrière (2010), which discuss the permanence of the printed book and its effects on the contemporary reading society, were also considered.